Stand structure and anatomical, physical and mechanical characterisation of sessile oak (Quercus petraea Liebl.) wood from central Italy aged coppices. - Brunetti, Michele; Macchioni, Nicola; Grifoni, Francesco; Lazzeri, Simona; Sozzi, Lorena; Cutini, Andrea (Annals of Silvicultural Research, 2020)
The present paper aims to implement the knowledge on sessile oak (Quercus petraea (Matt.) Liebl.) in Mediterranean area where, although present, for natural or anthropogenic causes, the species is rare. The focus is on two sessile oak stands in Tuscany (central Italy), classified as worthy of protection for their importance both in a local-national and European context. In addition to the environmental and stand structural characteristics, some technological properties of sessile oak wood grown there, comparing the obtained results to the bibliographic data were provided. The examined wood characteristics are anatomical parameters (growth ring thickness, earlywood and latewood thickness, fiber length, earlywood and latewood vessel diameter, amount of earlywood and latewood vessel) and the physical and mechanical parameters (density, modulus of elasticity, strength, hardness). No appreciable technological differences issued between the examined wood in the two stands and the wood from the same species, but from other Italian and French provenances, obtained from literature. Results highlighted, although managed as coppice in the past, the material is suitable for the reforestation of this endangered species in suitable areas, always taking into account that the quality of the wood is determined not only by the basic technological properties of a certain wood, but also, and mostly, by the growing conditions of the trees and particularly by the sylvicultural management of the stand.